Condiloma acuminado gigante de pene. Dilema terapéutico - Brau, Gabriel F.; Navarro Tuculet, Cecilia; Enz, Paula A.; Cabarcas Ávila, Freddy; Galimberti, Ricardo L. (Revista del Hospital Italiano de Buenos Aires, 2007)
-